Writing technical documents - Eunson, Baden (Milton, Qld : John Wiley and Sons, 1995)
This book is about: Technical documents: Who reads them?; Some basic techniques of writing skills; Communicating visually; Getting the facts; ...
Keywords: English language; Rhetoric; Technical writing; English language -- Technical English; English language -- Rhetoric; Technical writing